OP0120 Specific Identification of Anti-Citrullinated Glucose-6-Phospate Isomerase Peptide (CCG) Antibodies Associated with HLA-DRB1 SE and Disease Activity in Patients with RA. (23rd January 2014) - Umeda, N.; Matsumoto, I.; Inoue, A.; Tanaka, Y.; Kondo, Y.; Tsuboi, H.; Suzuki, T.; Tsuchiya, N.; Sumida, T.
Abstract : Background: Anti-citrullinated protein antibodies (Abs) (ACPA) are identified as a hallmark of diagnosis and disease progression in sera of patients with RA. Although several ACPA targeting citrullinated fibrinogen, collagen type II, a-enolase and vimentin have been confirmed, their pathogenic role are still mostly elusive due to the lack of association to disease activity. Anti-glucose-6-phosphate isomerase (GPI) Abs is confirmed as arthritogenic in mouse model, and only few patients with RA possessed them, however, anti-cyclic citrullinated GPI peptide (CCG) Abs have not been characterized. Objectives: To identify and characterize anti-CCG Abs in patients with RA. Methods: 1) Nine arginine-bearing peptide sequences in human GPI were selected and cyclic citrullinated GPI peptides (CCG-1∼-9) were constructed. Five unmodified GPI peptides were also synthesized (G-1, -2, -3, -4 and -7). Samples were obtained from patients with RA (n=208), SLE (n=101), Sjögren's syndrome (SS; n=101), and from healthy control subjects (n=174). Abs against CCG-1∼-9 and G-1, -2, -3, -4, -7 were measured by ELISA, and anti-citrullinated a-enolase-1 (CEP-1), and anti-CCP Abs were also examined. 2) Patients with RA were genotyped for HLA-DRB1. The numbers of shared epitope (SE) alleles were counted and compared with positivity of anti-CCG Abs. 3) The levels of auto-Abs were compared before and after six month treatment with TNF antagonists in 58 RA patients (infliximab, n=41, etanercept, n=15, adalimumab, n=2). Results: 1) Anti-CCG-2, -4 and -7 Abs were detected in 25.5%, 33.2% and 37.0% patients with RA, respectively. These Abs were specific for RA (specificity, 98.1% ∼ 99.7%). Abs against five unmodified GPI peptides were detected only 0% ∼ 3.8% patients with RA. Altogether, 44.2% and 86.1% of RA sera were positive for anti-CEP-1 and -CCP Abs. The levels of anti-CCG-2, -4 and -7 Abs were correlated with that of anti-CCP and anti-CEP-1 Abs. 2) Anti-CCG-2, -4 and -7 Abs were significantly correlated with the presence of HLA-DRB1 SE alleles (P<0.01, P<0.05 and P<0.001, respectively). 3) Treatment with TNF antagonists significantly reduced the levels of anti-CCG-2 and -7 Abs (P<0.001, P<0.05, respectively), but not of anti-CEP-1 Abs. Conclusions: This is the first report documenting the presence of anti-CCG-1∼-9 Abs in patients with RA. Anti-CCG-2 and -7 Abs could be considered as markers for the diagnosis of RA and its disease activity. Disclosure of Interest: None Declared